THE STUDY OF MORPHOLOGICAL CHANGES IN THE SKIN CAUSED BY TATTOOING AND THE STUDY OF MORPHOMETRIC CHARACTERISTICS WHEN USING POMEGRANATE SEED OIL - Shuxrat J. Teshaev; Jasur X. Ozodov (Central Asian Journal of Medicine, 2024)
Tattooing is a popular form of body art, but its impact on skin morphology remains a subject of study. This research investigates the morphological alterations in the skin caused by tattooing and explores the morphometric characteristics when utilizing pomegranate seed oil. The study aims to enhance understanding of the effects of tattooing on skin health and to explore potential natural remedies. Materials and methods involved the examination of skin samples before and after tattooing, with the application of pomegranate seed oil on designated areas. Morphological changes were assessed using histological techniques, while morphometric analysis was conducted to quantify alterations. Results indicate significant differences in skin morphology post-tattooing, with notable improvements in skin health observed in areas treated with pomegranate seed oil. This research sheds light on the potential benefits of natural products in mitigating the effects of tattooing on skin health.